Representations of violent pasts in memorial museums. Ethical reflection and history education (Las representaciones de pasados violentos en museos memoriales. Reflexión ética y enseñanza de la historia). Issue 3 (2nd July 2020) - Bermudez, Angela; Epstein, Terrie
ABSTRACT: This paper explores the ways in which memorial museums open opportunities for a critical understanding of violent pasts. We build off the concept of 'popular uses of the past' to discuss the importance of including ethical reflection in history education. Next, we present an original rendering of the ways in which violence is often normalized in school history textbooks and derive analytical categories that are used to examine if and how historical narratives in memorial museums normalize or interrogate violence. We analyse the narratives of the Exile Memorial Museum in La Jonquera (Spain) and the International Slavery Museum in Liverpool (England) to shed light on the ways the exhibits invite ethical reflection. In the last section we discuss how schools may benefit from incorporating resources like museum exhibits that open up rather than minimize discussions of historical violence and its relation to the present and future.